2015
DOI: 10.1007/s00784-015-1576-3
|View full text |Cite
|
Sign up to set email alerts
|

Short fibre-reinforced composite for extensive direct restorations: a laboratory and computational assessment

Abstract: The restoration of extensive cavities in posterior tooth is a challenge for the clinicians and the choice of the material that increases the fracture strength of tooth-restoration complex is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
3
7
1
1
Order By: Relevance
“…Comparing the fracture resistance, although the fracture values of all SFRC were higher than the other groups, the difference was not significant. This result is in accordance with Barreto et al who compared the fracture resistance of CFC and SFRC + CFC in premolar teeth and Fráter et al who found higher fracture toughness and load bearing capacity with SFRC compared with CFC without any significant differences. On the other hand, Gaourishi et al and Kemaloglu et al found higher fracture results with SFRC comparing with CFC.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the fracture resistance, although the fracture values of all SFRC were higher than the other groups, the difference was not significant. This result is in accordance with Barreto et al who compared the fracture resistance of CFC and SFRC + CFC in premolar teeth and Fráter et al who found higher fracture toughness and load bearing capacity with SFRC compared with CFC without any significant differences. On the other hand, Gaourishi et al and Kemaloglu et al found higher fracture results with SFRC comparing with CFC.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the previously‐mentioned studies, Atalay et al., Rocca et al., and Barreto et al. reported that the incorporation of SFRC inside the cavity of posterior destroyed teeth restored with thick PFC resin overlays is not useful to increase their load‐bearing capacity or to yield a better failure mode after load to fracture . They explained that the discrepancy between their studies and previous studies stemmed from a difference in the thickness of overlay PFC composites, loading set‐up, and the adhesive system used.…”
Section: Resultsmentioning
confidence: 86%
“…20,41 Fatigue strength of teeth restored with this material also did not differ from that of a conventional composite. 42 The only report on the material's K Ic showed a significantly higher value, compared to other commercial composites. 43 In order to understand the effect of fibers on composite properties, it is important to look at the variables involved in fiber reinforcement using systematic experimental designs.…”
Section: Strategy 2a: Fiber-reinforced Compositesmentioning
confidence: 88%